Designing More Effective 9 Segment Display for Bengali and English Digits - Miah, Mohammad Badrul Alam; Rahman, Md. Habibur; Islam, Md. Nazrul (Engineering International, 2015)
Seven-segment display is well-known for displaying the English numerals form 0-9. In this paper 9-segment display for both Bengali and English digits have been proposed. Our proposed 9-segment display is more effective than the previously proposed 10-segment, 11-segment, 16-segment and 8-segment display for both Bengali and English as well as 9-segment, 10-segment and 18-segment display Bengali digits. It is an improvement of previously proposed segment display for both Bengali and English digits.